2016
DOI: 10.1177/2040622316658459
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of management modality in Saudi patients with type 2 diabetes to components of metabolic syndrome, γ glutamyl transferase and highly sensitive C-reactive protein

Abstract: Background:The aim of this study was to investigate the relationship among management modality, glycemic control, components of metabolic syndrome (MS) and serum levels of γ glutamyl transferase (GGT) and C-reactive protein (CRP) in patients with type 2 diabetes (T2DM). Methods: Patients with T2DM, not suffering from diabetes complications, were recruited from outpatients clinics at two hospitals in Jeddah. Anthropometric measurements and blood pressure (BP) were taken. A treatment plan was recorded. Fasting b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Serum GGT is an enzyme thought to be associated with oxidative stress and increased risk of cardiovascular disease in diabetic patients [36]. In this cohort, the median serum GGT level was higher in patients with increased WC compared with those with normal WC.…”
Section: Avci a çEtinkaya Journal Of Biosciences And Medicinesmentioning
confidence: 66%
See 1 more Smart Citation
“…Serum GGT is an enzyme thought to be associated with oxidative stress and increased risk of cardiovascular disease in diabetic patients [36]. In this cohort, the median serum GGT level was higher in patients with increased WC compared with those with normal WC.…”
Section: Avci a çEtinkaya Journal Of Biosciences And Medicinesmentioning
confidence: 66%
“…There was also a positive correlation in male diabetics between WC and serum GGT levels at a mild and statistically significant correlation. There are studies in the literature that this correlation exists [37] and does not exist [36]. And there were studies demonstrating no beneficial effect of losing WC on serum GGT [37] [38].…”
Section: Avci a çEtinkaya Journal Of Biosciences And Medicinesmentioning
confidence: 99%
“…In an earlier study on T2DM patients, we reported a correlation between GGT level and dyslipidemia [ 54 ]. Unfavourable lipid profiles in patients with NAFLD had been reported in previous studies [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of creatinine (CRE), uric acid (UA), blood glucose (Glu) and triglyceride (TG) in plasma were determined using the classic enzymatic methods 19 22 . Cholesterol level was measured using automated enzymatic methods 23 . High-density lipoprotein (HDL) cholesterol concentration was measured by enzymatic colorimetric methods with commercially available kits, and low-density lipoprotein (LDL) cholesterol concentration was measured by homogeneous assay 24 .…”
Section: Methodsmentioning
confidence: 99%